Measurement of the WW production cross section with dilepton final states in pp̄ collisions at s=1.96TeV and limits on anomalous trilinear gauge couplings - Abazov, V. M. (2009)
We provide the most precise measurement of the WW production cross section in pp̄ collisions to date at a center of mass energy of 1.96 TeV, and set limits on the associated trilinear gauge couplings. The WW→ℓνℓ ′ν (ℓ, ℓ′=e, μ) decay channels are analyzed in 1fb-1 of data collected by the D0 detector at the Fermilab Tevatron Collider. The measured cross section is σ(pp̄→WW)=11.5±2.1(stat+syst) ±0.7(lumi)pb. One- and two-dimensional 95 C.L. limits on trilinear gauge couplings are provided. © 2009 The American Physical Society.